“TOXICOPATHOLOGICAL STUDIES OF ACETYL SALICYLIC ACID (ASA) IN BROILER CHICKS” - Sunanda Pandey; Priya D. Ghodasara; Jaynudin H. Khorajiya; Vandip. D. Chauhana; D. J. Ghodasara; B. P. Joshi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Study was undertaken to assess the effects of Acetyl salicylic acid (ASA) administration in 80 day old cobb broiler chicks which were divided in to 4 groups. ASA was administered at the dose rate of 400, 1600 and 4000 ppm orally (Group II to IV) through feed for 21 consecutive days along with distilled water as vehicle in Group I. Birds of group III and IV were slightly dull, depressed and anorectic. Slow growth rate and blood mixed faecal droppings were observed in few birds of group IV with maximum mortality of 5 %. A dose dependent reduction in body weight and feed consumption and dose dependent significant (p < 0.05) increase in kidney: body weight ratio was observed in group III and IV as compared to control. There was significant decrease in the values of AKP, PCV, TEC and Hb in group IV. Histopathological section revealed damage to the intestine, kidney and lungs. It can be concluded that ASA at very high doses i.e. 4000ppm for longer duration can cause bone damage and anemia which can lead to mortality.